Form finding of corrugated shell structures for seismic design and validation using non-linear pushover analysis. (15th February 2019) - Michiels, Tim; Adriaenssens, Sigrid; Dejong, Matthew
Highlights: A form finding method for the design of corrugated shells in seismic areas is presented. The method considers vertical and horizontal accelerations from the start. Geometries are obtained for a series of masonry shells. Non-linear pushover analysis is used to validate the form finding method. The pushover capacities increase significantly compared to reference shells. Abstract: The geometry of shell structures plays an essential role in their capacity to withstand earthquakes. However seismic loading is rarely considered when determining the overall geometry of shells. This paper presents a novel form finding methodology for the conceptual seismic design of corrugated shells. The method ensures that a compression load path exists to carry lateral earthquake accelerations by deriving shell geometries from a series of funicular polygons obtained through a graphic statics procedure for combined gravity and horizontal loads. While the method can be applied to any material that resists compressive stresses, it is employed in this paper to find the shapes of corrugated thin-tile masonry shells. Non-linear pushover analysis is then used to quantify lateral capacity and evaluate form finding results in terms of material efficiency to resist lateral loads. The analysis furthermore provides insights regarding the collapse mechanisms and flow of forces. It is demonstrated that the lateral capacity before cracking in the corrugated shell shapes is up to 79% higher than the capacity of a non-form-found reference shell shapes considering identical material use. All form-found shells were found to fail through a similar collapse mechanism which is defined by four crack zones. The location of these crack zones can be manipulated through the form finding process and identify the locations where reinforcement could be most efficiently introduced. Finally, the flow of forces within the form-found shells is used to propose alternative designs that provide additional openings in the shell surface while maintaining similar seismic capacity. Thus, the paper provides a new approach for the conceptual design of safe corrugated shell structures in earthquake prone areas.